2006
DOI: 10.1038/ncb1440
|View full text |Cite
|
Sign up to set email alerts
|

SPPL2a and SPPL2b promote intramembrane proteolysis of TNFα in activated dendritic cells to trigger IL-12 production

Abstract: Homologues of signal peptide peptidase (SPPLs) are putative aspartic proteases that may catalyse regulated intramembrane proteolysis of type II membrane-anchored signalling factors. Here, we show that four human SPPLs are each sorted to a different compartment of the secretory pathway. We demonstrate that SPPL2a and SPPL2b, which are sorted to endosomes and the plasma membrane, respectively, are functional proteases that catalyse intramembrane cleavage of tumour necrosis factor alpha (TNFalpha). The two protea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
211
2
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 179 publications
(223 citation statements)
references
References 32 publications
9
211
2
1
Order By: Relevance
“…Mass spectrometry revealed that rhomboid proteolysis is notably site-specific, in contrast to other intramembrane proteases (Fraering et al, 2004; Fluhrer et al, 2006; Friedmann et al, 2006; Sato et al, 2006). In fact, cleavage of the Drosophila EGF ligand Spitz always proceeded between the first two residues (AS) of its TM segment even with eight diverse rhomboid proteases and in bacterial, insect and human cells (and different organelles) that harbor lipid composition differences (Fast, 1966) (Figure 1A, also see Figure 1—figure supplement 1A).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mass spectrometry revealed that rhomboid proteolysis is notably site-specific, in contrast to other intramembrane proteases (Fraering et al, 2004; Fluhrer et al, 2006; Friedmann et al, 2006; Sato et al, 2006). In fact, cleavage of the Drosophila EGF ligand Spitz always proceeded between the first two residues (AS) of its TM segment even with eight diverse rhomboid proteases and in bacterial, insect and human cells (and different organelles) that harbor lipid composition differences (Fast, 1966) (Figure 1A, also see Figure 1—figure supplement 1A).…”
Section: Resultsmentioning
confidence: 99%
“…Intensively studied is γ-secretase, an aspartyl intramembrane protease that releases signaling domains from the membrane, including the intracellular domains of the Notch receptor and the amyloid-β precursor protein (APP) implicated in Alzheimer's disease (De Strooper et al, 1998, 1999; Wolfe et al, 1999). Homologous signal peptide peptidases function in immunity by liberating signaling domains of TNFα and FasL (Fluhrer et al, 2006; Friedmann et al, 2006; Kirkin et al, 2007). Site-2 proteases are metalloenzymes that release transcription factors from the membrane to regulate membrane biogenesis and stress responses in diverse organisms from bacterial pathogens to man (Rawson et al, 1997; Makinoshima and Glickman, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Two recent publications report TNFa intramembrane cleavage by SPPL2a and SPPL2b, 36,37 which triggers expression of the pro-inflammatory cytokine interleukin-12 (IL-12) by activated human dendritic cells. 37 Together with our data on FasL processing by SPPL2a, these results indicate an emerging important role of SPPLs in RIP of TNF family members.…”
Section: Discussionmentioning
confidence: 99%
“…Several transmembrane proteins are subjected to intramembrane proteolysis, as a result of which the ICD is released for signaling to the nucleus 31,37 (also see references therein). Our findings of a similar FasL RIP by ADAM10 and SPPL2a prompted us to investigate whether the FasL ICD (liberated by SPPL2a cleavage) could translocate to the nucleus and influence gene transcription.…”
Section: Discussionmentioning
confidence: 99%
“…Two of these genes in particular are worth noting. NOD1 and SPPL2A both play an important role in the immune response and the development of inflammatory disease 37,38 and are therefore plausible candidate risk genes for PE and CVD.…”
Section: Discussionmentioning
confidence: 99%